MANAGING CHANGES IN PUBLIC SECTOR: CONCEPTUALIZING COMPONENT OF THE OVERALL PROCESS OF PUBLIC ADMINISTRATION (IN EDUCATION) - Semenets-Orlova I.A. (Pressing Problems of Public Administration, 2016)
The article is dedicated to the features of the evolution of educational change management as part of organizational theory, theory of organizational development and as an independent branch of science. The author has analyzed change management (as a form of social management) and state (public) management of educational changes (as part of the overall process of state (public) management (in education field). The article determined planned and emergent educational changes.